Decline of Mediterranean oak trees and its association with Phytophthora cinnamomi: a review - Camilo-Alves, Constança (2014)
Mortality events in cork and holm oaks have occurred in the Mediterranean basin since the beginning of the XX century, but severity of decline increased during the 1980s. By that time, the exotic soil borne pathogen Phytophthora cinnamomi was often recovered from declining stands and since then it has been considered the main factor associated with decline. This work analyses data concerning P. cinnamomi surveys in cork and holm oaks trees, pathogenicity tests carried out in controlled experiments, studies about the influence of site characteristics in tree decline and approaches to control the disease. Results of field surveys showed that the pathogen is widespread and pathogenicity tests suggested that host susceptibility to the pathogen is moderate when seedlings are in appropriate watering conditions, particularly cork oaks. Occurrence of decline is also associated with soil characteristics that interfere with root expansion and water retention. We assessed the relative importance of each factor involved in decline and revised the role of P. cinnamomi in cork and holm oak decline.